El Aberto - la caminata de un pueblo - Morgen, Markus von (Germany : Kunsthochschule fur Medten Koln, 2009)
El Alberto lies in a hilly, cactus-covered region about 170 km north of Mexico City. Most of the inhabitants left the poverty-stricken village in the mid 1980s. Crossing the border to the US illegally, many found work on the construction sites of theme hotels in Las Vegas. Threatened by extinction through mass migration, the village has since passed a law requiring every man born in El Alberto to complete one year of unpaid social service. Anyone who does not comply forfeits any property he may have in the village. Furthermore, family members still living in the village have their water and electricity supply cut off. Year after year men return from the US to do their community service, living on the money they have saved before heading north again once the year is completed.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films